Pollutant transport among California regions. Issue 12 (20th June 2013) - Angevine, Wayne M.; Brioude, Jerome; McKeen, Stuart; Holloway, John S.; Lerner, Brian M.; Goldstein, Allen H.; Guha, Abhinav; Andrews, Arlyn; Nowak, John B.; Evan, Stephanie; Fischer, Marc L.; Gilman, Jessica B.; et al.
Abstract : [1] Several regions within California have significant air quality issues. Transport of pollutants emitted in one region to another region may add to the impact of local emissions. In this work, Lagrangian particle dispersion model simulations show the amounts of tracers that are transported within and among four regions, Southern California, the San Francisco Bay Area, the Central Valley, and the rest of the state. The simulations cover May and June of 2010, the California Research at the Nexus of Air Quality and Climate Change experiment period. Tracers of automobile emissions and one type of agricultural emission are used. Tracer mixing ratios are compared to airborne and ground‐based measurements. The age of tracers in each location is also presented. Vertical profiles and diurnal cycles help to clarify the transport process. As is well known, Southern California emissions are transported to the east and affect the desert areas, and Bay Area automobile emissions are an important source of pollutants in the San Joaquin Valley. A novel result is that the Southern California Bight is filled with a mixture of well‐aged carbon monoxide tracer from Southern California and the Bay Area. Air over the Bight is also affected by the agricultural emissions represented by the agricultural tracer, dominantly from the Central Valley where its sources are largest. There is no indication of transport from Southern California to the Central Valley. Emissions from the Central Valley do make their way to Southern California, as shown by the agricultural tracer, but automobile emissions from the Valley are insignificant in Southern California. Key Points: WRF/FLEXPART is used to describe transport patterns in California Tracer age (time since emission) is shown Southern California and the Bay Area influence air in the Southern California Bight